2017
DOI: 10.1097/psy.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray Matter Volumes as Related to Psychomotor Slowing in Adults with Type 1 Diabetes

Abstract: OBJECTIVE Psychomotor slowing is a common cognitive complication in type 1 diabetes (T1D), but its neuroanatomical correlates and risk factors are unclear. In non-diabetic adults, smaller gray matter volume (GMV) and presence of white matter hyperintensities (WMH) are associated with psychomotor slowing. We hypothesize that smaller GMV in prefronto-parietal regions explains T1D-related psychomotor slowing. We also inspect the contribution of microvascular disease and hyperglycemia. METHODS GMV, WMH, and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
(79 reference statements)
3
5
0
Order By: Relevance
“…The functional connectivity of the basal ganglia is altered in response to hypoglycemia in individuals with T1DM (Bolo et al 2015b), and changes in basal ganglia volume have been documented in a pediatric sample of individuals with T1DM(Northam et al 2009). These data build upon findings in the basal ganglia by our group (Hughes et al 2013; Hwang et al 2016; Nunley et al 2017) and others (Bolo et al 2015a; Cranston et al 2001; Gallardo-Moreno et al 2015; Heikkilä et al 2010; Moulton et al 2015; Pell et al 2012; Rooijackers et al 2016; Seaquist 2015; Selvarajah et al 2011).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The functional connectivity of the basal ganglia is altered in response to hypoglycemia in individuals with T1DM (Bolo et al 2015b), and changes in basal ganglia volume have been documented in a pediatric sample of individuals with T1DM(Northam et al 2009). These data build upon findings in the basal ganglia by our group (Hughes et al 2013; Hwang et al 2016; Nunley et al 2017) and others (Bolo et al 2015a; Cranston et al 2001; Gallardo-Moreno et al 2015; Heikkilä et al 2010; Moulton et al 2015; Pell et al 2012; Rooijackers et al 2016; Seaquist 2015; Selvarajah et al 2011).…”
Section: Discussionsupporting
confidence: 87%
“…In non diabetic populations, the basal ganglia are especially vulnerable to SVD due to their poor collateral vascularization (watershed areas) (Pantoni 2010). The basal ganglia appear especially vulnerable to T1D, as shown by our group (Hughes et al 2013; Hwang et al 2016; Nunley et al 2017) and others (Bolo et al 2015a; Cranston et al 2001; Gallardo-Moreno et al 2015; Heikkilä et al 2010; Moulton et al 2015; Pell et al 2012; Rooijackers et al 2016; Seaquist 2015; Selvarajah et al 2011). Abnormalities in the basal ganglia is of concern in T1D, because of their role in hypoglycemia unawareness(Bolo et al 2015a; Cranston et al 2001; Heikkilä et al 2010; Rooijackers et al 2016), as well as in decision making(Mogenson et al 1980), thus potentially affecting diabetes management.…”
Section: Introductionsupporting
confidence: 71%
“…We found that psychomotor speed was slower in both older individuals with type1 and older individuals with type 2 diabetes compared with control subjects. Psychomotor speed is typically impaired in type 1 diabetes and may be tied to basal ganglia or white matter integrity (30). In our earlier research using voxel-based morphometry, we showed hyperglycemiaassociated reduced gray matter density in posterior cingulate, superior temporal gyrus, and parahippocampal gyri (23).…”
Section: Discussionmentioning
confidence: 63%
“…Many previous studies have reported gray matter volume alterations in many different brain regions in patients with T1DM, which includes the superior frontal gyrus, middle frontal gyrus, middle temporal gyrus, thalamus and cerebellum (5)(6)(7)(8)(9). These changes are thought have some relations with the cognitive impairment in patients with T1DM.…”
Section: Introductionmentioning
confidence: 98%